2018
DOI: 10.1371/journal.pone.0197174
|View full text |Cite
|
Sign up to set email alerts
|

Species identification and connectivity of marine amphipods in Canada’s three oceans

Abstract: Monitoring the distribution of marine biodiversity is a crucial step to better assess the impacts of global changes. Arctic marine fauna is dominated by amphipods in terms of abundance and biomass. These peracarids are an important marine order of crustaceans but the number of species found in the different Canadian oceans is currently unknown. Furthermore, most species are difficult to identify due to poor taxonomic descriptions and morphological convergence. The aim of this study was to assess the species di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 86 publications
(128 reference statements)
2
22
1
Order By: Relevance
“…The maximum inter-specific distance of 5.51% was observed between Victoriopisa chilkensis and Orchestia platensis (table S2). The inter-specific maximum (0.16%) and minimum (5.51%) values observed were lower than what those reported in Canadian amphipods (0.6% and 18.07%, respectively) (Tempestini et al, 2018). The interspecific values observed for deep-sea amphipod species (13%) (Knox et al, 2012) was also higher than the maximum interspecific values observed in this study.…”
Section: Sequence Analysis and Species Identificationcontrasting
confidence: 66%
See 2 more Smart Citations
“…The maximum inter-specific distance of 5.51% was observed between Victoriopisa chilkensis and Orchestia platensis (table S2). The inter-specific maximum (0.16%) and minimum (5.51%) values observed were lower than what those reported in Canadian amphipods (0.6% and 18.07%, respectively) (Tempestini et al, 2018). The interspecific values observed for deep-sea amphipod species (13%) (Knox et al, 2012) was also higher than the maximum interspecific values observed in this study.…”
Section: Sequence Analysis and Species Identificationcontrasting
confidence: 66%
“…As seen in few marine amphipod species of Canadian waters (Tempestini et al, 2018), we detected no stop codons in the COI sequences. Mean GC content was 39.25+0.93% which is slightly higher than the Arctic amphipod's GC content of (32.9%) (Tempestini et al, 2018). Table 2 provides descriptive statistics for the distribution of nucleotide frequencies.…”
Section: Sequence Analysis and Species Identificationsupporting
confidence: 58%
See 1 more Smart Citation
“…Currently, no uniform threshold value has been established for species delineation, and there is no single "universal" DNA barcode that captures all eukaryotic life. Even within a single animal order there can be large differences in this value between families (Tempestini et al 2018). Despite these issues, DNA barcoding and nextgeneration metabarcoding can reveal genetic diversity and are useful tools for the description and cataloguing of biodiversity.…”
Section: Utilization and Promotion Of Taxonomic Expertise And Speciesmentioning
confidence: 99%
“…Currently, no uniform threshold value has been 223 established for species delineation, and there is no single "universal" DNA barcode that captures 224 all eukaryotic life. Even within a single animal order there can be large differences in this value 225 between families (Tempestini et al 2018). Despite these issues, DNA barcoding and next-226 generation metabarcoding can reveal genetic diversity and are useful tools for the description and 227 cataloguing of biodiversity.…”
mentioning
confidence: 99%